Who is in the garden - Geatches, Hazel (United Kingdom : Aardman Animations limited, 2021)
Is there a big animal in the garden?
"Who is in the Garden?" likely presents a simple mystery or exploration for young, beginner English readers, featuring Timmy from Timmy Time as he investigates who or what might be in a garden. The story would likely use repetitive language and focus on common garden elements. Location: 2A
Keywords: Garden book